A comparative ride performance of passive, semi-active and active suspension systems for off-road vehicles using half car model - BenLahcene, Zohir; Hasbullah, Faried; Faris, Waleed Fekry (Inderscience Enterprises Ltd., 2014)
The work aims to study the performance of suspension systems for off-road vehicles. Three type of suspensions-passive, hybrid semi-active and Linear Quadratic Regulator (LQR) active suspension systems are presented using half-car model. These systems are compared in terms of ride quality, handling, road holding and ability to support vehicle static weight through transient and statistical analyses. Results indicate the responses of the proposed LQR active system to random road excitation relative to the passive system are better than the hybrid semi-active system in terms of the criteria mentioned above